THE ROLE OF THE VARIETAL RESOURCES OF SOFT SPRING WHEAT OF THE WESTERN SIBERIA IN THE SOLUTION OF FOOD SECURITY OF THE REGION - A. A. Kazak; Yu. P. Loginov (Зерновое хозяйство России, 2018)
The Western Siberia is one of the largest regions of the country in the production of soft spring wheat. The weather-climatic conditions of the place allow yielding grain with high content of gluten and protein, suitable to the food use. The research results of the institutions and long-term agronomic experience showed that as the Western Siberia has a variety of weather-climatic zones, fertile soil, their profitable arrangement, it needs a wide range of spring wheat varieties, well adapted to the local conditions. The kind of a variety is of primary importance in the Siberian plant-growing. The article gives the analysis of the registered varieties of soft spring wheat according to their origin, speed of maturing and grain quality. It has been noted that 71 varieties out of 81 registered ones belong to the local breeding (87,6%). The rest 10 varieties (12,4%) belong to the breeding in another regions. The foreign varieties aren’t used in the sowings. The last decades the breeders and geneticists of the region have been successfully solving the problem of tolerance of the varieties to lodging. The sowings of the most varieties of spring wheat with the grain productivity of 4-5 t/ha do not lodge. The genes of winter varieties and of short-stem spring wheat varieties from the collection of Vavilov ARRIR are used in the breeding experiments. The problem of the development of rapid maturing varieties with high quality of grain is being successfully solved. The early and middle-early varieties make up 24,7%, the varieties with the quality of grain make up 32,1%, the valuable varieties make up 45,6%. The institutions SibRIR, SibRIA, ARIA, OmSAU and Northern Zauralie RIA contributed a lot into the development of the varieties of valuable and strong wheat. In the past the Western Siberia was a consumer of food wheat, but nowadays the region is a reliable supplier of the grain on the external market. The scientists face the problem of developing the varieties tolerant to stem and leaf rust and other diseases, adapted to the harsh Siberian conditions.